Overview of Mothers’ Knowledge on Infant and Young Child Feeding (IYCF) Among Stunted Toddlers in Tatui Village (Journal of Social And Education Research, 2024)
Malnutrition remains one of the leading causes of child morbidity and mortality, particularly during the first five years of life. Inappropriate infant and young child feeding (IYCF) practices contribute significantly to the high prevalence of stunting in Indonesia. This study aimed to describe the knowledge of mothers of stunted toddlers regarding IYCF in Tatui Village, working area of Kosiwo Public Health Center, Yapen Islands Regency. The study employed a quantitative descriptive design with a cross-sectional approach. The population consisted of 45 mothers of stunted toddlers, selected using a total sampling technique. Data were collected using a structured questionnaire developed based on WHO and Ministry of Health guidelines. The results showed that most respondents had low knowledge about IYCF before the educational intervention but demonstrated a substantial improvement afterward. The findings indicate that nutrition education plays a crucial role in enhancing mothers’ understanding of appropriate feeding practices, including exclusive breastfeeding, complementary feeding, and balanced nutrition. Strengthening community-based nutrition education programs is essential to empower mothers and support stunting prevention efforts in Yapen Islands Regency.